From response to preparedness: Enhancing community-led disaster risk management in Malawi: Key findings and policy implications - Kayamba-Phiri, Fundi; Khulumbo, Burnnet; Nkhulembe, Maziko; Babu, Suresh Chandra; Ahsan, Sairana (International Food Policy Research Institute, 2023)
Key Messages: - Directing resources towards early warning systems and community sensitization mitigates the impact of natural disasters on vulnerable communities, prioritizing proactive measures over reactive responses. - To ensure effective and sustainable disaster risk management (DRM) initiatives, allocating resources to bolster district-level DRM structures in alignment with community-led resource mobilization efforts is crucial. - Recognizing the pivotal role of youth increases community anticipatory capacity through comprehensive disaster risk management training. Innovative approaches such as theatre for development foster civic engagement, community dialogue, and resource mobilization. - Inclusive participatory planning processes should embrace indigenous early warning information. In-vesting in automated community-based early warning systems, particularly focusing on agriculture and nutrition, facilitates timely decision-making and harnesses local wisdom. - To reduce vulnerability among low-income communities, forging partnerships with the private sector is crucial. Micro-insurance and asset options can be explored, empowering communities to enhance their resilience without imposing undue burdens.